Zeeman deceleration of metastable nitrogen atoms - Toscano, J; Softley, T; Dulitz, K; Tauschinsky, A (University of Oxford, 2016)
Raw data, simulations and analysis code for the evidence presented in the paper "Zeeman deceleration of metastable nitrogen atoms" by Katrin Dulitz, Jutta Toscano, Atreju Tauschinsky and Timothy P Softley published in J. Phys. B: At. Mol. Opt. Phys. 49 (2016) 075203 (6pp)